Teknik Fermentasi Buah Berbasis Fruit Classic Enzyme Untuk Mengatasi Masa Simpan Buah Melalui Minuman Organik - Maria Ulfah; Ade Ihtiar; Alifia Fillah; Gita Sari; Lilla Faizsyahrani (Indonesian Journal of Applied Technology, 2025)
The short shelf life of fruits often leads to quick spoilage, making them unsuitable for further use. Fruit Classic Enzyme offers an alternative to extend fruit shelf life through the principles of functional food biotechnology. This study aims to identify the techniques of Fruit Classic Enzyme in prolonging fruit freshness through organic fermented beverages and to explore its potential as an entrepreneurial product. The research employed a qualitative descriptive method, describing the quality and characteristics of the Fruit Classic Enzyme product. The results revealed the production process, laboratory analysis, and various derivative products, including Fruit Classic Enzyme Pure, Ready to Drink, Anti-Inflammatory, and Jelly variants. In conclusion, Fruit Classic Enzyme serves as an effective innovation to extend fruit shelf life using functional food biotechnology fermentation, resulting in diverse organic beverage products.